EVALUATION OF AZADIRACHTA INDICA LEAVES EXTRACT FOR ANTI-ALLERGIC POTENTIAL - A. Helen Sonia; Pawar Kavita Yogesh; Sonali V Uppalwar; Romila Antony; B. Sathya; Payal Rani; Rajiv Bharti; Biresh Kumar Sarkar; Dhammshila L Devhare (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
This study investigates the antiallergic potential of Azadirachta indica leaves extract as a natural remedy for allergic conditions. Azadirachta indica, commonly known as Neem, has a history of medicinal use in traditional medicine systems. The ethanolic extract was prepared from the leaves and evaluated in allergen-induced allergic reactions using animal models and in-vitro process. The extract demonstrated significant antiallergic effects, reducing histamine release, suppressing pro-inflammatory cytokines, and enhancing immunomodulatory activity. These findings support the traditional use of Azadirachta indica and its potential as an antiallergic agent. The presence of bioactive compounds like nimbin, nimbidin, and azadirachtin may contribute to its antiallergic properties. Further research is needed to elucidate the underlying mechanisms and evaluate the extract's safety and efficacy in human subjects. If proven effective, Azadirachta indica leaves extract could offer an affordable and accessible alternative for managing allergic conditions.